Assessment of the Effect of Methanolic Herbal Extract on Cocoon Parameters and Tensile Properties of Silk Fiber Spun by Beauveria bassiana Infected Muga Silkworm, Antheraea assamensis Helfer - Saharia, Sanghamitra; Kalita, Shibani; Kalita, Dimpimoni; Ojah, Anjumani; Bardoloi, Sunayan (Asian Journal of Biological and Life Sciences)
Aim: The current study was an attempt to combat white muscardine disease in muga silkworm (Antheraea assamensis Helfer) by utilizing herbal extract in an eco-friendly way. Materials and Methods: In this study, different cocoon parameters and tensile properties of silk fibres produced by 5th instar muga silkworm larvae infected from white muscardine disease caused by entomopathogenic fungus Beauveria bassiana were evaluated by treating with 10% methanolic rhizome extract of Curcuma longa (turmeric). The silkworms were topically inoculated with LC50 concentration (1.1×108 spore/mL) of the fungal spore suspension and then reared on a host plant sprayed with C. longa extract. Results: Different cocoon parameters such as cocoon weight, pupal weight, shell ratio, filament length, non-breakable filament length, denier, reliability and raw silk percentage were measured and observed to be improved significantly after treating the infected silkworm with the plant extract when compared to the normal control group. Estimation of the weight of sericin and fibroin proteins in cocoons was also accounted for in the study which appeared to be significantly enhanced after treatment of the larvae with C. longa Linn. extract. The tensile properties of the muga fibres also followed the same trend of improvement after treatment with the herbal extract. The silk fibre produced by C. longa-treated larvae exhibited better tensile strength and breaking strain percentage to a significant extent. Conclusion: Thus, the study reflected the curative effect of C. longa on the commercial parameters of muga cocoons leading to better silk output probably by restraining the growth of fungal spores in the silkworm body.
Keywords: Beauveria bassiana; Cocoon; Curcuma longa; Muga silkworm